1997
DOI: 10.1021/bk-1997-0654.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Total Mercury and Methylmercury Levels in Scalp Hair and Blood of Pregnant Women Residents of Fishing Villages in the Eighth Region of Chile

Abstract: The extent of environmental exposure to mercury through the diet (i.e., by consumption of fish and seafood), of a population group having higher than average fish and seafood consumption was assessed between 1991 and 1994 in pregnant women (PW) and nursing women (NW) residing in selected fishing villages (FVs) along the coastal zone of the Eighth Region of Chile. The control population was an equivalent group with negligible seafood consumption. The samples were scalp hair collected from the occipital region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The average mercury level in hair we observed in fishermen of the Persian Gulf was lower than that in human hair from the Amazon regions (Passos et al 2003;Malm et al 1997; Barbosa 1997;Lebel et al 1997) and Japan (Feng et al 1998), but was comparable with the Hg concentrations reported in hair of fish consumers in Indonesia (Feng et al 1998), in North Atlantic women consuming whale meat (Weihe et al 2005), in Kuwaiti fishermen (ROPME 1999), and in Chilean (Brhun et al 1997) fish consumers. The average mercury level in fishermen's hair in our study was higher than the mercury levels in hair of children or women with low fish consumption in America (Weihe et al 2005), in China (Feng et al 1998), and in Korea (Lee and Lee 1999).…”
Section: Comparison With Literature Datasupporting
confidence: 76%
“…The average mercury level in hair we observed in fishermen of the Persian Gulf was lower than that in human hair from the Amazon regions (Passos et al 2003;Malm et al 1997; Barbosa 1997;Lebel et al 1997) and Japan (Feng et al 1998), but was comparable with the Hg concentrations reported in hair of fish consumers in Indonesia (Feng et al 1998), in North Atlantic women consuming whale meat (Weihe et al 2005), in Kuwaiti fishermen (ROPME 1999), and in Chilean (Brhun et al 1997) fish consumers. The average mercury level in fishermen's hair in our study was higher than the mercury levels in hair of children or women with low fish consumption in America (Weihe et al 2005), in China (Feng et al 1998), and in Korea (Lee and Lee 1999).…”
Section: Comparison With Literature Datasupporting
confidence: 76%
“…The characteristics of the selected studies are provided in Table 3 and Table 4 (both available at: http://www.who.int/ bulletin/volumes/92/04/13-116152). 74,75 Chile, 76 China, [77][78][79][80][81] Colombia, 82 Italy, 83,84 Kazakhstan, 85 Mexico, 87 Morocco, 88 Nicaragua, 89 Norway, 115 the Republic of Korea, 86 Romania, 90 Slovakia, 81,91 Sweden, 92 Taiwan, China, 93 the United States 94 and Venezuela (Bolivarian Republic of), 95 the pooled central THHg median biomarker was 0.8 µg/g (upper bound: 4.6). In 14 subpopulations consuming fish periodically from non-industry-contaminated waters in Botswana, 96 Canada, [97][98][99][100][101][102] Norway, 115 Portugal, 117 Spain, 118 Sweden, 81,92,[112][113][114]119 the United Kingdom of Great Britain and Northern Ireland 120,121 and the United States 122-131 was 0.4 µg/g (upper bound: 2.9).…”
Section: Selected Studiesmentioning
confidence: 99%
“…In this study, the mean hair mercury concentration reached 1.81 mg kg -1 (corresponding to mothers who live in the coastal region) which was significantly associated with frequency of fish consumption. In other report (Bruhn et al, 1994), total mercury content in scalp hair was analyzed in nursing women (South of Chile) with normal to high fish and seafood consumption as well as in women with negligible or no fish and seafood consumption. The results showed a higher concentration hair mercury of woman's with high fish consumption.…”
Section: Introductionmentioning
confidence: 99%